2003
DOI: 10.1074/jbc.m300081200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of N and C Termini in the Antifreeze Activity of Winter Flounder (Pleuronectes americanus) Antifreeze Proteins

Abstract: Antifreeze proteins (AFPs) are found in many marine fish and have been classified into five biochemical classes: AFP types I-IV and the antifreeze glycoproteins. Type I AFPs are ␣-helical, partially amphipathic, Alarich polypeptides. The winter flounder (Pleuronectes americanus) produces two type I AFP subclasses, the liver-type AFPs (wflAFPs) and the skin-type AFPs (wfsAFPs), that are encoded by distinct gene families with different tissue-specific expression. wfsAFPs and wflAFPs share a high level of identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…While activity levels have been reported to increase with helical content for two homologues of the flounder AFPs (59), there is no clear correlation between helicity and activity. For example, highly helical mutants of type I AFPs can show marked decreases in activity (58) and specific mutations in skin-type AFP have been shown to increase activity by 15%, while reducing the helical content from 80 to 60% (59). The data presented for rSS3 confirm that there is not a simple correlation of this type, and that to some extent the determinants of hysteresis are somewhat more subtle.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…While activity levels have been reported to increase with helical content for two homologues of the flounder AFPs (59), there is no clear correlation between helicity and activity. For example, highly helical mutants of type I AFPs can show marked decreases in activity (58) and specific mutations in skin-type AFP have been shown to increase activity by 15%, while reducing the helical content from 80 to 60% (59). The data presented for rSS3 confirm that there is not a simple correlation of this type, and that to some extent the determinants of hysteresis are somewhat more subtle.…”
Section: Discussionmentioning
confidence: 91%
“…Several AFPs have been shown to maintain their fold at very low temperatures and an increase in R-helical content is observed with a decrease in temperature in other type I AFPs (58). While activity levels have been reported to increase with helical content for two homologues of the flounder AFPs (59), there is no clear correlation between helicity and activity. For example, highly helical mutants of type I AFPs can show marked decreases in activity (58) and specific mutations in skin-type AFP have been shown to increase activity by 15%, while reducing the helical content from 80 to 60% (59).…”
Section: Discussionmentioning
confidence: 99%
“…10 It was reported that termini of the HPLC6 isoform possess greater helix-stabilizing ability compared to the HPLC2 isoform, leading to a 50% difference in the thermal hysteresis activity between these two AFPs. 11 These results suggested that helical stabilization of the N and C termini is the critical component for antifreeze activity of the type I AFP. 11 It was recently reported that flexibility of the C-terminal region causes a loss of thermal hysteresis activity because its dynamic nature strongly prevents binding to the ice surface.…”
mentioning
confidence: 92%
“…11 These results suggested that helical stabilization of the N and C termini is the critical component for antifreeze activity of the type I AFP. 11 It was recently reported that flexibility of the C-terminal region causes a loss of thermal hysteresis activity because its dynamic nature strongly prevents binding to the ice surface. 12 Here, to further understand the correlation between the dynamic properties and function of type I AFPs, we performed NMR hydrogen exchange experiments on the winter flounder type I AFP (HPLC6 isoform) (Fig.…”
mentioning
confidence: 92%
“…1B), identified the requirement for a hydrophobic face on the peptide to maintain thermal hysteresis. While molecular simulations of the interaction of TTTT with the fluid ice–water interface has assisted in understanding the balance between hydrophobic and hydrophilic residues in ice growth inhibition [11], the subtle role(s) of the helix‐dipole and positioning of individual residues within the chain remain poorly understood [12]. Thus, attempts to design synthetic AFPs related to TTTT have been of limited success to date [13,14].…”
Section: Introductionmentioning
confidence: 99%